Chromosome-level genome assembly of tetraploid Chinese cherry (Prunus pseudocerasus) - Wei Zhang; Jing Wang; Xuncheng Wang; Xuwei Duan; Junbo Peng; Xiaoming Zhang; Qikai Xing; Kaichun Zhang; Jiye Yan (Scientific Data)
Abstract Chinese cherry belongs to the family Rosaceae, genus Prunus, and has high nutritional and economic value. ‘Duiying’ is a Chinese cherry variety local to Beijing, and has better performance than sweet cherry in terms of disease resistance. However, disease resistance resources of ‘Duiying’ have not been fully exploited partially due to the lack of a high-quality genome. In this study, we report a high-quality chromosome-scale genome assembly for Chinese cherry ‘Duiying’, by combining PacBio HiFi, Bionano and Hi-C sequencing data. The assembled genome has a size of 1035.19 Mb, with a scaffold N50 of 28.99 Mb, and 978.61 Mb (94.54%) assembled into 32 pseudochromosomes. A total of 547.16 Mb (52.86%) sequences were identified as repetitive sequences, and 114,451 protein-coding genes were annotated. Moreover, a total of 1635 microRNA (miRNA), 6637 transfer RNA (tRNA), 38,258 ribosomal RNA (rRNA), and 169 small nuclear RNAs (snRNA) genes were identified. The genome assembly presented here provides valuable genomic resources to enhance our understanding of genetic and molecular basis of Chinese cherry.